UNITY IN DIVERSITY: PHILOSOPHICAL TRADITIONS OF INDIA AND WEST - Tola, Fernando (2005)
This article gives an affirmative answer to western positions against theexistence of philosophy in India. It is shown that topics familiar to Greeksand Europeans were treated in India well deep into the XVIth century.Misleading opinions describing Indian thinking as being irrational whenopposed to westem rationality, although both systems might havedisplayed irrational traits, will also be discussed. It is accepted though thatcomparisons don't go further than modern times when westemphilosophers took their own different ways.